2009
DOI: 10.1007/s10649-009-9207-z
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service primary teachers’ conceptions of creativity in mathematics

Abstract: . (2010) 'Pre-service primary teachers' conceptions of creativity in mathematics.', Educational studies in mathematics., 73 (2). pp. 143-157. Further information on publisher's website:http://dx.doi.org/10.1007/s10649-009-9207-z Publisher's copyright statement:The nal publication is available at www.springerlink.com Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(53 citation statements)
references
References 43 publications
0
45
0
8
Order By: Relevance
“…Consiste en construir algo nuevo liberándose previamente de los modos de pensar establecidos, viendo distintas posibilidades y aplicando una gama variada de conocimientos matemáticos (Bolden, Harries & Newton, 2010). La justificación para llevar a cabo esto es la flexibilidad cognitiva, una de las tres funciones mentales principales que están implicadas en la solución creativa de problemas (Ausubel, 1963(Ausubel, , 2000.…”
Section: Creatividad Y Educación Matemáticaunclassified
“…Consiste en construir algo nuevo liberándose previamente de los modos de pensar establecidos, viendo distintas posibilidades y aplicando una gama variada de conocimientos matemáticos (Bolden, Harries & Newton, 2010). La justificación para llevar a cabo esto es la flexibilidad cognitiva, una de las tres funciones mentales principales que están implicadas en la solución creativa de problemas (Ausubel, 1963(Ausubel, , 2000.…”
Section: Creatividad Y Educación Matemáticaunclassified
“…It has been defined in various ways, with some definitions focusing on the process and others stressing the creative product (Haylock, 1987;Kattou, Kontoyianni, & Christou, 2009;. Producing something authentic or original via a personal activity is a common basis of these definitions (Bolden et al, 2010;Sriraman, 2004). Guilford (1950) made a distinction between convergent thinking, which provides only one correct solution to a problem, and divergent thinking, which involves creatively generating multiple solutions to a problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Student-directed creativity relates to the opportunities given that foster student creativity. Bolden et al (2010) found that prospective elementary teachers understand two types of creativity in mathematics lessons: creative teaching and creative learning. Creative teaching involves the creative use by teachers of resources and the application of mathematics to everyday examples.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations